AK-cowboy - Wayne, Joanna (Toronto ; New York : Harlequin, 2011)
"Tyler Ledger was as unsure of Julie Gillespie's motives for being at his family's Texas ranch as he was of the reception he'd receive when he came face-to-face with his estranged father. Still, he agreed to help the enticing reporter solve a murder if she agreed to stay out of trouble. Julie was on a mission, and she wasn't going to be sidetracked by romantic entanglements--even if Tyler was proving more irresistible by the minute. But with his leave of absence over soon, the soldier's time in Texas was coming to an end ... and Julie's would, too, if they didn't find the killer before she became the next target"--Publisher.
Keywords: Murder -- Investigation -- Fiction; Soldiers -- Fiction; Women journalists -- Fiction; Fathers and sons -- Fiction